Generalização da sequência curta de Fadell-Neuwirth para os grupos de tranças de superfícies - Dutra, Éderson Ricardo Frühling (Universidade Federal de São Carlos, 2014)
The objective of this work is to study the braid groups on topological surfaces as well as studying a generalization of the Fadell-Neuwirth short exact sequence. We treated also the existence of a cross-section for the Fadell-Neuwirth s generalized fibration, in particular, we are concerned in the case when the surface is equal the sphere S2.
Keywords: Matemática; Topologia algébrica; Teoria das tranças; CIENCIAS EXATAS E DA TERRA::MATEMATICA